Re-branding as the need for business success - Kostyuchenko, Nadiya (My University, 2014)
Rebranding is the process by which a product or service developed with one brand, company or product line affiliation is marketed or distributed with a different identity. This may involve radical changes to the brand's logo, brand name, image, marketing strategy, and advertising themes. These changes are typically aimed at the repositioning of the brand/company, usually in an attempt to distance itself from certain negative connotations of the previous branding, or to move the brand up market. Re-branding can be applied to new products, mature products, or even products still in development.
Keywords: business; marketing strategy; re-branding; ребрендинг; маркетингова стратегія; бізнес; бизнес; маркетинговая стратегия